Postharvest ripening of newly harvested corn: Structural, rheological, and digestive characteristics of starch. (15th April 2023) - Hu, Nannan; Zhao, Chengbin; Li, Sheng; Qi, Weihua; Zhu, Jinying; Zheng, Mingzhu; Cao, Yong; Zhang, Hao; Xu, Xiuying; Liu, Jingsheng
Abstract: Newly harvested corn was stored at 25 °C and 55% relative humidity, the changes in the structure, rheological and digestive properties of corn starch during postharvest ripening were studied. The postharvest ripening process of corn resulted in a reduction in the content of amylose and an increase in the proportion of double-helical structures, short-range orderliness and relative crystallinity. These structural changes significantly improved the thermal stability of the starch and its ability to form gels. The lowest hydrolysis rate constant was demonstrated for corn starch at 30 days, indicating that proper post-ripening could help corn starch to form a stronger gel network structure and slow down the digestibility. The results of the study will contribute to a better understanding of the changes in the structure and properties of corn starch during the postharvest ripening, which provided a pathway for the rational processing and utilization of corn starch and even corn food at different postharvest ripening stages. Graphical abstract: Image 1 Highlights: Postharvest ripening of corn was carried out at 25 °C and 55% relative humidity. Postharvest ripening process resulted in a more compact structure of corn starch. Highest thermal stability and lowest digestibility appeared at 30 days of storage. Postharvest ripening increased the apparent viscosity and viscoelasticity of starch. Regulating post-ripening process of corn contributed to processing of starch.